World Compendium of Healthcare Facilities and Nonprofit Organizations - Elahi, Ebby (Taylor & Francis, 2022)
World Compendium of Healthcare Facilities and Nonprofit Organizations is the most comprehensive index of critical information on healthcare facilities and nonprofits in 72 low and lower-middle-income countries as classified by the World Bank. Presented in an easily accessible format and organized in 72 country chapters, the compendium allows stakeholders to better identify where healthcare services are available and where additional resources are needed.